An evolutionary strategy for Δ E − E identification. (11th September 2017) - Schmidt, K.; Wyszyński, O.
Abstract: In this article we present a proof of concept of using an evolutionary strategy in Δ  E  −  E identification procedure on simulated data. The algorithm combines a generative model of Δ  E  −  E relation and a Covariance Matrix Adaptation Evolutionary Strategy (CMA-ES). The CMA-ES is a stochastic and derivative-free method employed to search parameter space of the model by means of a fitness function. The article describes details of the method along with results of an application on simulated labeled data.